A moderated mediation model for body-positive online content and body image among adolescents. (September 2022) - Kvardova, Nikol; Machackova, Hana; Smahel, David
Abstract: Body-positive online content (BPOC) has recently become widespread, yet the factors that explain its association with body satisfaction have scarcely been studied. The current study investigates the indirect association between the self-reported frequency of viewing BPOC and body satisfaction through body appreciation and the moderating roles of body-ideal internalization, self-esteem, intentional searching, and gender. Utilizing survey data from 1530 Czech adolescents aged 13–18 ( M =15.4, SD =1.7, 50 % girls), the present study found limited support for an indirect connection between the frequency of viewing BPOC and body satisfaction through body appreciation. Nonetheless, an indirect association appeared among adolescents with average and above-average frequencies for intentional searching for BPOC. Other investigated moderating factors were not significant. The present findings suggest that BPOC may be positively associated with body image, but only for those who deliberately search for it. The study highlights the importance of individual moderating factors in the context of BPOC and the remaining research gaps, such as the examination of its various types and aspects and their relationship with body image. Highlights: The association between viewing body-positive online content and body image was negligible. Intentional searching strengthened the role of body-positive online content. Body-ideal internalization, self-esteem, and gender were not significant moderators.